Optical, thermal and radiation shielding properties of B2O3–NaF–PbO–BaO–La2O3 glasses - Shaaban, Kh. S.; Alomairy, Sultan; Al-Buriahi, M. S. (Journal of materials science. Materials in electronics, 2021)
The techniques of melt-quenching have been used to generate 53B 2 O 3 —2NaF—27PbO – ( 20 - x ) BaO— x La 2 O 3 ( 0 ≤ x ≥ 15 ) g l a s s s y s t e m . XRD patterns have been established the amorphous character of glass samples. There is a clear evidence of the role of the La 2 O 3 modifier in the glass network. The thermal characteristics have been identified to increase with an increase in La 2 O 3 content. Increasing La 2 O 3 increases the linear and non-linear optical bandgap energy and the Urbach energy. By adding La 2 O 3 to the glass samples, the refractive index, molar polarizability, polarizability, and optical basicity increased. The bulk modulus and the glass transition temperature increased because of the increase in bond strength. The number of bonds per unit increased with the increase in La 2 O 3 content because of the modifier character of La 2 O 3 in the glass samples. Many optical parameters ( ε ∞ ), ( ε o ), χ ( 1 ) , χ ( 3 ) and ( n 2 ) as a function of linear and non-linear E opt have been obtained. The extent of shielding in this article has been examined with the increment in La 2 O 3 at the expense of BaO. The results correspond with similar studies conducted before.